Serum DDT in malaria vector control sprayers in Mato Grosso State, Brazil - Eliana Freire Gaspar de Carvalho Dores; Leandro Carbo; Adley Bergson Gonçalves de Abreu
DDT was used intensively in vector control programs in Mato Grosso State until 1997. The present study aimed to determine DDT concentrations in blood samples from Brazilian National Health Foundation workers in Mato Grosso. Blood samples were analyzed from 41 sprayers, 20 drivers, and 14 unexposed workers, collected in June 1999 and October 2000 in two regions of the State (Sinop and Cáceres). Sprayers and drivers were occupationally exposed, and no significant differences were found in serum DDT levels between these two groups in either region. Likewise, no significant differences were found in p,p'DDE and total DDT levels between Cáceres and Sinop. However, p,p'DDT levels were higher in Sinop due to the intensive use of this insecticide in the region in recent years. The two regions together showed the following results: total DDT ranging from 7.50µg/L to 875.5µg/L (median = 135.5µg/L) for sprayers; from 34.5µg/L to 562.3µg/L (median = 147.7µg/L) for drivers; and from undetected to 94.8µg/L (median = 22.5µg/L) for unexposed workers.